2022
DOI: 10.1007/s10238-022-00949-3
|View full text |Cite
|
Sign up to set email alerts
|

Real-world clinical outcomes of treatment with molnupiravir for patients with mild-to-moderate coronavirus disease 2019 during the Omicron variant pandemic

Abstract: It is unclear whether molnupiravir has a beneficial effect on vaccinated patients infected with the Omicron variant of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). We here evaluated the efficacy of molnupiravir in patients with mild-to-moderate coronavirus disease 2019 (COVID-19) during the Omicron variant surge in Fukushima Prefecture, Japan. We enrolled patients with mild-to-moderate COVID-19 who were admitted to hospitals between January and April, 2022. Clinical deterioration after admissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Three real-world studies performed in Hong Kong and Japan evaluated clinical effectiveness of nirmatrelvir-ritonavir and molnupiravir in people hospitalized with mild-to-moderate COVID-19 disease (Table 2 ). The large majority of included patients were more than 60 years old, and had adequate vaccination rates ranging from 10 to 80% [ 12 , 37 , 38 ]. Compared with matched controls, molnupiravir and nirmatrelvir-ritonavir were consistently associated with 40–55% lower risk of clinical deterioration.…”
Section: Treatment Of Patients Hospitalized With Mild-to-moderate Dis...mentioning
confidence: 99%
See 1 more Smart Citation
“…Three real-world studies performed in Hong Kong and Japan evaluated clinical effectiveness of nirmatrelvir-ritonavir and molnupiravir in people hospitalized with mild-to-moderate COVID-19 disease (Table 2 ). The large majority of included patients were more than 60 years old, and had adequate vaccination rates ranging from 10 to 80% [ 12 , 37 , 38 ]. Compared with matched controls, molnupiravir and nirmatrelvir-ritonavir were consistently associated with 40–55% lower risk of clinical deterioration.…”
Section: Treatment Of Patients Hospitalized With Mild-to-moderate Dis...mentioning
confidence: 99%
“…Compared with matched controls, molnupiravir and nirmatrelvir-ritonavir were consistently associated with 40–55% lower risk of clinical deterioration. Moreover, molnupiravir was associated with 52–69%, and nirmatrelvir-ritonavir 66–90% lower risk of death respectively [ 12 , 37 , 38 ].…”
Section: Treatment Of Patients Hospitalized With Mild-to-moderate Dis...mentioning
confidence: 99%
“…The study stated that molnupiravir was safe and that it constitutes an alternative for such risk factors for COVID-19 [ 105 ]. Additionally, Suzuki et al reported a study utilizing 1929 micron-infected COVID-19 patients’ real-world data [ 106 ]. After 1:3 propensity score matching, clinical deterioration was compared between molnupiravir users (230 participants) and nonusers (690 participants).…”
Section: Pharmacovigilance Profile Of Molnupiravirmentioning
confidence: 99%
“…We identified 21 relevant papers and presented their recorded data in Table 1 . Eight studies from the T United States [6][7][8][9][10][11][12][13], five from South Africa [18][19][20][21][22], three from the United Kingdom [15][16][17], and three from other countries [14,[23][24][25][26] compared the severity of COVID-19 between the Omicron variants and previous variants. Two studies from Japan reported the proportion of severe COVID-19 cases without comparing different variants.…”
Section: Re Su Ltsmentioning
confidence: 99%